Percutaneous dilatational tracheostomy compared with conventional surgical tracheostomy in neurosurgery intensive care unit - Rai, Shiwani; Adhikari, Suman; Bhandari, Prabin; Koirala, Krishna Prasad; Karmacharya, Balgopal; Yogi, Nikunja (Asian Journal of Medical Sciences, 2020)
Background: Tracheostomy is a commonly performed procedure in intensive care units (ICU). Percutaneous dilatation tracheostomy (PDT) has achieved wide acceptance recently since its first introduction by Ciagila in 1985. Aims and Objective: The current study was designed and aimed to compare conventional tracheostomy (CT) with percutaneous dilatation tracheostomy using Grigg’s GWDF technique in terms of operative timing, duration of ICU and hospital stay and complications. Materials and Methods: A prospective, single blinded, randomized study was done in between April 2019 to December 2019. Patients were randomly assigned into CT group and PDT group of 32 patients in each group. Data were recorded in terms of demographics, preoperative diagnosis, GCS, comorbidities, ICU stay, hospital stay, decanulation time, operative time and various complications. Data were compared using student’s t test for continuous variables and Chi-squared test or Fisher’s exact test for categorical variables. Data were analyzed using IBM SPSS statistics version 20. Results: Mean operative time in CT group was 35.00±9.56 min and in PDT group was 18.17±8.78 min and the difference was statistically significant (p=0.00). Similarly, there was statistically significant difference in overall complications in between conventional and percutaneous dilatation tracheostomy group. However, there was no significant difference in terms of total ICU stay, hospital stay and tracheostomy decanulation time in between these group. There was no statistical difference in between individual category of complications in between the two study groups. Conclusion: Percutaneous dilatation tracheostomy is equally safe and effective as conventional tracheostomy but with lower incidence of overall complications and faster to perform.